Anti‐IL‐31 receptor antibody is shown to be a potential therapeutic option for treating itch and dermatitis in mice. (5th September 2014) - Kasutani, K; Fujii, E; Ohyama, S; Adachi, H; Hasegawa, M; Kitamura, H; Yamashita, N
<x xml:space="preserve">Abstract</x> Background and Purpose IL‐31, which is described as a pruritogenic cytokine, is linked to the itching that is associated with allergic and non‐allergic eczema, but the precise pruritogenic mechanism of IL‐31 and its potential as a therapeutic target for atopic dermatitis (AD) have not been determined. Experimental Approach We investigated the effects of existing drugs on the scratching behaviour induced by an i.v. injection of IL‐31 to clarify whether IL‐31 induced pruritus indirectly. In addition, we studied the effects of an anti‐IL‐31 receptor α subunit (anti‐IL‐31 receptor α) neutralizing antibody on chronic pruritus‐inducing dermatitis in an AD‐like model to determine whether IL‐31 not only induces scratching behaviour, but is also the causative factor in an AD phenotype. Key Results The scratching behaviour induced by an i.v. injection of IL‐31 was inhibited by pretreatment with an anti‐IL‐31 receptor α‐neutralizing antibody. In contrast, it was not inhibited significantly by a non‐sedative antihistamine (terfenadine), immunosuppressants (dexamethasone and tacrolimus), or a μ‐opioid receptor antagonist (naloxone). The anti‐IL‐31 receptor α‐neutralizing antibody reduced the ear swelling and dermatitis score in a chronic pruritus‐inducing AD‐like model. Moreover, treatment with the anti‐IL‐31 receptor α‐neutralizing antibody showed therapeutic effects on the dermatitis even if it was injected after the disease had developed. Conclusions and Implications Anti‐IL‐31 receptor α is a potential novel therapeutic approach for escaping from the itch–scratch cycle and also a treatment for dermatitis in AD.